Intercultural communication and success in business - Dubinko Svetlana Alekseevna (EDP Sciences, 2021)
Effective business communication requires a certain degree of cross-cultural awareness and tolerance both on the ethnic and organizational levels. Communication patterns vary from culture to culture according to values, beliefs and traditional rules for interacting with others, which makes up a learned behavior. These deep-rooted factors lie inside cultural differences and change very slowly if ever as compared to those which are more likely to be on the surface, like food, tastes, art. The latter are more easily adopted or erased in today’s global economy. The purpose of the study is to show that the internal traits compose different layers of metaphoricity in the language and, if understated, may lead to complexities or failures in business communication. Based on the experience of working in an international environment, which is analyzed by many scientists, and on the results of the study performed it can be noted that cross-cultural awareness and tolerance imply a variety of intelligences beyond (IQ), including emotional, cultural, social, and collective types of intelligence.